The NEPTON test: System Overview and functionality - Alexander, Christopher; Papadima-Sophocleous, Salomi (My University, 2007)
Over the past few decades, a fairly large literature examining various aspects of computer-assisted language testing (CALT) has been developed. The findings indicate that many institutions are now using new technologies for their language testing practices. There are often detailed discussions about the test development processes, the effectiveness of such tests and evaluation of their success. Less is known, however, about their particular features and how the mechanisms ‘behind the scenes’ make them work and easy to use. The purpose of this article is to give an overview of the key features and mechanisms of New English Placement Test Online (the NEPTON test).
Keywords: NEPTON test; computer-assisted language testing (CALT)